Evaluation of Sustainable Land Management Practices in Kaharo Subcounty Kabale District. - Nasaasira, Blair (Kabale University, 2024)
This study was carried out to examine the sustainable land management practices in Kaharo Sub-County, Kabale District. This was guided by the following research objectives:(i) identify the land management practices, (ii) detennine the effects of identified land management practices and (iii) examine the perception of people about the identified land management practices in Kaharo Sub-County Kabale District. Questionnaire and interview guide were the main instruments for data collection in the study area. The population for the study comprised of farmers and sub county officials. The total population of the study was 99 respondents. Simple random sampling and purposive sampling methods were employed. The major findings of the study revealed that mixed farming, terracing, tree planting, mulching, crop rotation, fertilizer application and minimum tillage was the most land management practices identified in the study area. The effects of land management practices identified in the study area were; reducing soil erosion, improving soil fertility, controls crop pest and diseases, reduces soil compaction, reduce leaching of nutrients and increase soil water uptake and the farmers have knowledge about land management practices in the study area knowing that crop rotation maintains soil fertility, land management practices help in reducing land degradation covering the surface with grass or crop residues reduce and respondents noted that terracing helps us to reduce run-off and rate of erosion. The study recommends that Land management practices are currently being used by farmers but have potential to improve crop production. Policy makers should be aware that the level of practice of the SLM was still very poor in the study area, policy should be formulated that will enforce land users (farmers) to adopt and practice the SLM technologies.